ANALISIS PEMILIHAN KARIR MAHASISWA AKUNTANSI YANG MENGIKUTI MAGANG UNTUK BERKARIR DI BIDANG AKUNTANSI (Studi Kasus pada Mahasiswa Program D3 Jurusan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Shofwa Fathina; Sudarno Sudarno (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to analyse the accountancy student’s career choice after completing an internship to pursue career in accountancy. This study use job attributes, person-job fit, and person-organization fit as independent variable, then analyzed that affection to person-career fit as dependent variable. The population of this study was the accounting student’s diploma programs of economics and business faculty at diponegoro university. The research data collection using questionnaire survey. The sampling method are purposive sampling. The criteria are the students must be completing their internship. The sample used in this study was 72 samples. Structural Equation Modelling—Partial Least Square used to be statistical analysis. The results of this study indicate that person-organization fit had direct effect to person-career fit. Another results are person-organization fit affect person-career fit through job attributes. This study also find out that person-organization fit affect person-career fit through person-job fit.